Lithium battery positive electrode material as well as preparation method and application thereof
By designing the lithium battery positive electrode material of LiaNixCoyMzNpO2 compound, using spherical particle structure and collaborative sintering technology, the problem of poor thermal stability of layered ternary positive electrode material is solved, and the high discharge specific capacity and safety is achieved, which improves the lithium battery safety performance and energy density.
Patent Information
- Application Number
- CN202310805962.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-03
- Publication Date
- 2025-01-07
AI Technical Summary
The thermal stability of the layered ternary positive electrode material is poor, which leads to the problem of thermal runaway in lithium batteries under the external thermal effect, reducing the safety of electric vehicles, and it is difficult to take into account both high discharge specific capacity and safety.
The compound of LiaNixCoyMzNpO2 is used as the cathode material of lithium battery. Through specific chemical composition and structural design, secondary microspheres of spherical particles are formed, combined with the synergistic effect of sheet-like precursors and Group VA element modifiers to adjust the sintering temperature and time. A structure in which strips of primary particles are arranged in the radial direction is formed.
The high discharge specific capacity of the lithium battery positive electrode material, the first week of Coulomb efficiency and the high thermal runaway trigger temperature are achieved, and the safety performance and energy density of the battery are improved.
Smart Images

Figure CN119275247A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of lithium batteries, and in particular to a lithium battery positive electrode material and a preparation method and application thereof. Background Art
[0002] New energy vehicles are an important means to achieve the "dual carbon" green development goals. With the promotion and popularization of new energy vehicles, the market demand for electric vehicles with long driving range is becoming more and more urgent. However, as the driving range increases, electric vehicles are gradually experiencing safety accidents such as spontaneous combustion, and the safety challenges of electric vehicles are becoming increasingly greater.
[0003] The performance of electric vehicles is mainly determined by the lithium batteries used, and the cathode material is one of the key components of lithium batteries, which determines the key indicators of power batteries such as energy density and safety. Among the currently commercialized cathode materials such as olivine-structured LiFePO4, spinel-structured LiMn2O4, layered LiCoO2 and layered ternary cathode materials, layered ternary cathode materials have higher theoretical capacity. When used in lithium batteries, they can improve the range of electric vehicles and are a research hotspot for high-performance lithium battery cathode materials.
[0004] CN114656000A discloses a nickel-cobalt-manganese-oxide lithium material, which reduces the Li / Ni mixing by doping the transition metal layer and the lithium layer with antimony of different valence states, thereby improving the stability of the bulk and surface from the material level. However, the thermal stability of the layered ternary positive electrode material is poor, and under the induction of external thermal effects, it is easy to cause thermal runaway problems in the battery, reducing the safety of the lithium battery. Therefore, it is urgent to solve the problem that it is difficult to balance the discharge capacity and safety of the layered ternary positive electrode material. Summary of the invention
[0005] The present invention aims to solve the problem that the capacity and safety of ternary positive electrode materials in the prior art are difficult to balance, and provides a lithium battery positive electrode material and its preparation method and application. The lithium battery positive electrode material of the present invention has the characteristics of high discharge specific capacity, high first cycle efficiency, and high thermal runaway temperature of the whole battery.
[0006] The first aspect of the present invention provides a lithium battery positive electrode material, comprising a chemical composition of Li a Ni x Co y M z N pCompounds of O2, where 0.9 ≤ a ≤ 1.2, 0 ≤ x ≤ 1, 0 ≤ y ≤ 1, 0 ≤ z ≤ 1, 0 < p ≤ 0.1, x, y, and z are not all 0 at the same time, and the values of a, x, y, z, and p satisfy the principle of electrical neutrality. The M is selected from at least one of the elements in Group VIIB or Group IIIA, and the N is selected from at least one of the elements in Group VA; the lithium battery cathode material is spherical, and the primary particles are strip-shaped with an aspect ratio of 1.05 - 20.00.
[0007] In the above technical solution, the chemical composition is Li a Ni x Co y M z N p In the compounds of O2, 0.5 ≤ x ≤ 0.95, 0 ≤ y ≤ 0.5, 0 ≤ z ≤ 0.5, 0 < p ≤ 0.05, x, y, and z are not all 0 at the same time, preferably x, y, and z are not 0 at the same time, and the values of a, x, y, z, and p satisfy the principle of electrical neutrality.
[0008] In the above technical solution, the primary particles are arranged along the radial direction of the sphere, and the median size of the spherical particles is 1 - 20 μm. Among them, the median size represents the particle diameter corresponding to when the cumulative particle size distribution percentage of the spherical particles reaches 50%.
[0009] In the above technical solution, the aspect ratio of the primary particles is 1.50 - 10.00, preferably 1.50 - 8.00.
[0010] In the above technical solution, the element in Group VIIB is preferably Mn, the element in Group IIIA is preferably Al, and the element in Group VA is selected from at least one of N, P, Sb, and Bi.
[0011] In the above technical solution, the M is preferably at least one of Mn and Al, and the N is preferably at least one of P, Sb, and Bi.
[0012] The second aspect of the present invention provides a preparation method of the above lithium battery cathode material, including:
[0013] Mixing a cathode material precursor, a lithium source, and a modifier containing an element in Group VA, and sintering to obtain the lithium battery cathode material.
[0014] In the above technical solution, the chemical composition of the cathode material precursor is Ni x Co y M z (OH)2, 0 ≤ x ≤ 1, 0 ≤ y ≤ 1, 0 ≤ z ≤ 1, preferably 0.5 ≤ x ≤ 0.95, 0 ≤ y ≤ 0.5, 0 ≤ z ≤ 0.5, x, y, and z are not all 0 at the same time, and the values of x, y, and z satisfy the principle of electrical neutrality.
[0015] In the above technical solution, the morphology of the positive electrode material precursor is microspheres formed by flake accumulation. The average thickness of the flakes is 1-500nm, preferably 1-200nm.
[0016] In the above technical solution, the lithium source is preferably selected from at least one of lithium nitrate (LiNO3), lithium chloride (LiCl), lithium carbonate (Li2CO3), lithium hydroxide (LiOH), lithium hydroxide monohydrate (LiOH·H2O), lithium oxide (Li2O), lithium acetate (CH3COOLi) and lithium oxalate (Li2C2O4).
[0017] In the above technical solution, the molar ratio of the positive electrode material precursor to the lithium source (in terms of Li element) is 1:(0.9-1.2).
[0018] In the above technical solution, the modifier containing the Group VA element is preferably selected from at least one of nitrates, chlorides, carbonates, hydroxides, oxides, acetates and oxalates containing the Group VA element.
[0019] In the above technical solution, the molar ratio of the positive electrode material precursor to the modifier containing the Group VA element (calculated as the Group VA element) is 1:(0-0.1) and is not 0, preferably 1:(0.001-0.05).
[0020] In the above technical solution, the sintering is programmed temperature sintering, the heating rate is preferably 0.5-10°C / min, the sintering temperature is 600-1000°C, preferably 720-900°C, the sintering time is 4-48h, preferably 8-24h, and more preferably 12-20h.
[0021] In the above technical solution, pre-sintering is performed before sintering, and the pre-sintering is programmed temperature sintering. The heating rate is preferably 0.5-10°C / min, the pre-sintering temperature is 300-600°C, preferably 450-550°C, and further preferably 450-530°C. The pre-sintering time is 1-10h, and preferably 4-8h.
[0022] The third aspect of the present invention provides the use of the above-mentioned lithium battery positive electrode material in a lithium battery.
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] 1. The positive electrode material of the lithium battery of the present invention is a secondary microsphere formed by arranging and aggregating primary particles along the radial direction of the spherical particles, wherein the primary particles are long strips with an aspect ratio of 1.05-20.0. The positive electrode material of the lithium battery of the present invention has excellent electrochemical performance and good safety performance, and has the advantages of high discharge specific capacity, high first-cycle coulomb efficiency and high thermal runaway trigger temperature.
[0025] 2. In the preparation process of the positive electrode material of the lithium battery of the present invention, the positive electrode material precursor with a flaky morphology, the lithium source, and the modifier containing the VA group element are mixed and sintered. During the sintering process, the crystallization process of the primary particles of the positive electrode material of the lithium battery is adjusted through the synergistic effect of the flaky morphology of the precursor and the modifier containing the VA group element, as well as the control of the sintering temperature and sintering time. The morphology of the primary particles of the positive electrode material of the lithium battery obtained is long strips, and is arranged along the radial direction of the secondary microspheres of the positive electrode material of the lithium battery. The material with this composition and structure is more conducive to the diffusion of lithium ions, and can improve the first week coulomb efficiency and discharge specific capacity of the material. At the same time, the material structure of this composition and structure is more stable, which can inhibit the formation and growth of microcracks in the material and has better safety.
[0026] 3. The lithium battery positive electrode material provided by the present invention can be used in high energy density and high safety lithium batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 is a SEM image of the lithium battery positive electrode material prepared in Example 1 of the present invention;
[0028] Figure 2 This is a SEM image of the cross section of the lithium battery positive electrode material prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0029] The technical solution of the present invention is described in detail below.
[0030] The first aspect of the present invention provides a lithium battery positive electrode material, the lithium battery positive electrode material comprises a chemical composition of Li a Ni x Co y M z N p O2 compound, the M is selected from at least one of the elements of Group VIIB or Group IIIA, and the N is selected from at least one of the elements of Group VA.
[0031] The lithium battery positive electrode material provided by the present invention has a chemical composition of Li a Ni x Co y M z N pCompounds of O2, where 0.9 ≤ a ≤ 1.2, 0 ≤ x ≤ 1, 0 ≤ y ≤ 1, 0 ≤ z ≤ 1, 0 < p ≤ 0.1, preferably 0.5 ≤ x ≤ 0.95, 0 ≤ y ≤ 0.5, 0 ≤ z ≤ 0.5, 0 < p ≤ 0.05, x, y, and z are not all 0 at the same time, preferably x, y, and z are all not 0, and the values of a, x, y, z, and p satisfy the principle of electrical neutrality.
[0032] In one embodiment of the present invention, preferably, M is selected from Mn and / or Al. That is, preferably, the chemical composition is Li a Ni x Co y M z N p The compound of O2 is Li a Ni x Co y MnzN p O2 or Li a Ni x Co y Al z N p O2.
[0033] The positive electrode material for lithium batteries provided by the present invention is a secondary microsphere formed by the aggregation of primary particles, and the primary particles are arranged along the radial direction of the secondary microsphere. The median particle size of the secondary microsphere is 1 - 20 μm.
[0034] The primary particles of the positive electrode material for lithium batteries provided by the present invention are strip-shaped, and the aspect ratio of the primary particles is 1.05 - 20.0, preferably 1.5 - 10.0, and more preferably 1.5 - 8.0. The aspect ratio of the primary particles is, for example but not limited to, 1.75, 1.95, 2.20, 2.45, 2.70, 2.95, 3.20, 3.45, 3.70, 3.95, 4.20, 4.45, 4.70, 4.95, 5.20, 5.45, 5.70, 5.95, 6.20, 6.45, 6.70, 6.95, 7.20, 7.45, 7.70, 7.95.
[0035] In a preferred embodiment of the present invention, the SEM image of the positive electrode material for lithium batteries is as shown in Figure 1 shown. From Figure 1 it can be seen that the positive electrode material for lithium batteries described in the present invention is spherical secondary particles, the median particle size of the spherical secondary particles is 10.3 μm, and the surface of the spherical particles contains a coating modification additive. The SEM image of the cross-section of the positive electrode material for lithium batteries is as shown in Figure 2 shown. From Figure 2 it can be seen that the primary particles are strip-shaped and the primary particles are arranged along the radial direction of the secondary microsphere.
[0036] In the present invention, the scanning electron microscope image (SEM) is obtained by a scanning electron microscope of the ZEISS Merlin model produced by the German ZEISS company.
[0037] The inventors of the present invention, through in-depth research on lithium battery positive electrode materials, have creatively obtained lithium battery positive electrode materials with the above-mentioned composition and structural characteristics in the process of preparing lithium battery positive electrode materials. The lithium battery positive electrode material with such characteristic composition and structure has higher discharge specific capacity and first-cycle coulombic efficiency, and has a higher thermal runaway trigger temperature when used in a full battery, and can be used in high-performance lithium batteries.
[0038] The second aspect of the present invention provides a method for preparing the above-mentioned lithium battery positive electrode material, comprising:
[0039] The positive electrode material precursor, the lithium source and the modifier containing the VA group element are mixed and sintered to obtain the positive electrode material for the lithium battery.
[0040] In the present invention, the chemical composition of the positive electrode material precursor is Ni x Co y M z (OH)2, 0≤x≤1, 0≤y≤1, 0≤z≤1, preferably 0.5≤x≤0.95, 0≤y≤0.5, 0≤z≤0.5, the values of x, y and z are not 0 at the same time, and the values of x, y and z satisfy the principle of electrical neutrality. As a non-limiting example, the typical chemical composition of the precursor can be Ni 0.5 Co 0.2 Mn 0.3 (OH)2、Ni 0.6 Co 0.2 Mn 0.2 (OH)2、Ni 0.8 Co 0.1 Mn 0.1 (OH)2、Ni 0.9 Co 0.05 Mn 0.05 (OH)2、Ni 0.95 Co 0.025 Mn 0.025 (OH)2、Ni 0.8 Co 0.15 Al 0.05 (OH)2, etc. The morphology of the positive electrode material precursor is a microsphere formed by flake accumulation, and the thickness of the flake is 1-500nm, preferably 1-200nm. The thickness of the flake is, for example but not limited to, 5nm, 10nm, 20nm, 30nm, 40nm, 50nm, 80nm, 100nm, 120nm, 150nm, 180nm.
[0041] In the present invention, the lithium source may be in the form of a lithium salt, and the lithium salt is preferably selected from at least one of lithium nitrate (LiNO3), lithium chloride (LiCl), lithium carbonate (Li2CO3), lithium hydroxide (LiOH), lithium hydroxide monohydrate (LiOH·H2O), lithium oxide (Li2O), lithium acetate (CH3COOLi) and lithium oxalate (Li2C2O4).
[0042] In the present invention, the mixing of the cathode material precursor and the lithium source can be achieved by a high-speed mixer, a ball mill, a V-type mixer, a mechanical stirrer, a plowshare mixer, a double-helix cone mixer, or the like.
[0043] In the present invention, the molar ratio of the positive electrode material precursor to the lithium source (in terms of Li element) is 1:(0.9-1.2). As a non-limiting example, when the molar number of the precursor is 1, the molar number of the lithium source in terms of Li element can be 0.9, 0.95, 1.00, 1.05, 1.10, 1.15, 1.20, and any value in the range formed by any two of these values.
[0044] In the present invention, the modifier containing the VA group element is preferably selected from at least one of nitrates, chlorides, carbonates, hydroxides, oxides, acetates and oxalates containing the VA group element. As a non-limiting example, the VA main group modifier can be at least one of ammonium nitrate, ammonium chloride, antimony acetate, antimony oxide, bismuth oxalate, bismuth carbonate, phosphorus oxide, etc.
[0045] In the present invention, the molar ratio of the positive electrode material precursor and the modifier containing the VA group element (calculated as the VA group element) is 1: (0-0.1) and is not 0. As a non-limiting example, when the molar number of the precursor is 1, the molar number of the modifying aid calculated as the VA element can be 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1, and any value in the range formed by any two of these values. Preferably, the molar ratio of the precursor and the modifier containing the VA group element (calculated as the VA group element) is 1: (0.001-0.05).
[0046] In the present invention, sintering is performed in an atmosphere furnace, and the sintering atmosphere may be at least one of air, oxygen, and an inert atmosphere such as nitrogen.
[0047] In the present invention, the sintering is programmed temperature sintering, and the sintering temperature is 600-1000°C, such as 600°C, 650°C, 700°C, 750°C, 800°C, 850°C, 900°C, 950°C, 1000°C and any range between any two values, more preferably, the sintering temperature is 720-900°C; the sintering time is 4-48h, such as 4h, 8h, 12h, 16h, 20h, 24h, 28h, 32h, 36h, 40h, 44h, 48h and any range between any two values, preferably, the sintering time is 8-24h, more preferably, the sintering time is 12-20h.
[0048] In the present invention, pre-sintering is carried out before the sintering, and the pre-sintering temperature is 300-600°C, such as 300°C, 350°C, 400°C, 450°C, 500°C, 550°C, 600°C and any range between any two values. Preferably, the roasting temperature is 450-550°C, and more preferably, the pre-sintering temperature is 450-530°C; preferably, the pre-sintering time is 1-10h, such as 1h, 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h and any range between any two values. More preferably, the pre-sintering time is 4-8h.
[0049] In the present invention, there is no particular limitation on the sintering heating rate, which is preferably 0.5-10°C / min, for example 0.5°C / min, 1°C / min, 2°C / min, 3°C / min, 5°C / min, 10°C / min, and any value in the range formed by any two of these values.
[0050] In the present invention, there is no special restriction on mixing the positive electrode material precursor, lithium source and modifier containing group VA element, and it can be achieved by high-speed mixer, ball mill, V-type mixer, mechanical stirring, plowshare mixer, double-helix cone mixer and the like.
[0051] The third aspect of the present invention provides a lithium battery positive electrode material prepared by the preparation method as described above.
[0052] The properties of the positive electrode material of the lithium battery have been described in detail in the first aspect and will not be repeated here.
[0053] The fourth aspect of the present invention provides the use of the above-mentioned positive electrode material for lithium batteries in lithium batteries. The lithium battery has: a positive electrode, including the above-mentioned positive electrode material for lithium batteries; a negative electrode; an electrolyte; and a separator. The positive electrode and the negative electrode can be prepared by coating and drying a composite for forming a positive electrode active material layer and a composite for forming a negative electrode active material layer on respective current collectors.
[0054] The positive electrode composite can be prepared by using a positive electrode active material, a conductive agent, a binder and a solvent.
[0055] The present invention has no specific restrictions on the conductive agent, as long as it has conductivity and remains stable within the charge and discharge range. The conductive agent can be at least one of acetylene black, ketjen black, artificial graphite, natural graphite, carbon tubes, graphene, superconducting carbon, carbon nanofibers, carbon dots, aluminum powder, nickel powder, titanium oxide, and conductive polymers.
[0056] The binder provides bonding between the positive electrode active material, the conductive agent and the current collector. The binder can be at least one of polyvinylidene fluoride (PVDF), polyvinyl alcohol (PVA), sodium carboxymethyl cellulose (CMC), styrene-butadiene rubber (SBR), water-based acrylic resin, polytetrafluoroethylene (PTFE), polyvinyl butyral (PVB), ethylene-vinyl acetate (EVA), vinylidene fluoride-tetrafluoroethylene-propylene lithium battery copolymer, vinylidene fluoride-hexafluoroethylene-tetrafluoroethylene lithium battery polymer, tetrafluoroethylene-hexafluoropropylene copolymer and fluorine-containing acrylic resin.
[0057] The present invention has no specific restrictions on the current collector, as long as it has suitable conductivity. The current collector can be aluminum, nickel, copper, titanium, silver, stainless steel and carbon materials. The current collector can be processed into various forms such as foil, sheet, film, net, hole, non-woven fabric, etc.
[0058] The solvent may be N-methylpyrrolidone.
[0059] The negative electrode composite can be prepared by using a negative electrode active material, a conductive agent, a binder and a solvent.
[0060] The present invention has no special restrictions on the negative electrode active material, which can be selected according to actual needs. The negative electrode active material can be at least one of artificial graphite, natural graphite, soft carbon, hard carbon, mesophase microspheres (MCMB), carbon fiber, lithium metal, silicon, silicon oxide, lithium metal alloy, and lithium titanate.
[0061] The conductive agent and binder of the negative electrode of the present invention are not particularly limited, and can be the same type and content as those used in preparing the positive electrode. The current collector of the negative electrode can also be aluminum, nickel, copper, titanium, silver, stainless steel and carbon materials. The current collector can also be processed into various forms such as foil, sheet, film, mesh, hole, non-woven fabric, etc.
[0062] The electrolyte of the present invention is a liquid electrolyte, and the liquid electrolyte contains a lithium salt and a solvent, wherein the lithium salt and the solvent are not specifically limited.
[0063] The solvent may be a non-aqueous solvent, for example, at least one of ethylene carbonate (EC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), propylene carbonate (PC), ethyl propyl carbonate (EPC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), methyl formate (MF), ethyl formate (Eft), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), and propyl butyrate (BP).
[0064] The lithium salt can be at least one of LiPF6 (lithium hexafluorophosphate), LiBF4 (lithium tetrafluoroborate), LiClO4 (lithium perchlorate), LiAsF6 (lithium hexafluoroarsenate), LiFSI (lithium bis(fluorosulfonyl)imide), LiTFSI (lithium bis(trifluoromethanesulfonyl)imide), LiTFS (lithium trifluoromethanesulfonate), LiDFOB (lithium difluorooxalatoborate), LiBOB (lithium bis(oxalatoborate), LiPO2F2 (lithium difluorophosphate), LiDFOP (lithium difluorooxalatophosphate), and LiTFOP (lithium tetrafluorooxalatoborate).
[0065] In order to improve the performance of lithium batteries, additives can be selectively added to the electrolyte, such as vinylene carbonate (VC), fluoroethylene carbonate (FEC), difluoroethylene carbonate (DFEC), tris(trimethylsilyl) phosphate (TMSP), sulfonate cyclic quaternary ammonium salt, ethylene sulfite (DTO), dimethyl sulfite (DMS), 1-propylene-1,3-sultone (PST), 4-propyl ethylene sulfate (PEGLST), diethyl sulfite (DES), adiponitrile (ADN), succinonitrile (SN), 1,3-propane sultone (1,3-PS), vinyl sulfate (DTD), 4-methylethylene sulfate (PCS), etc.
[0066] The separator is arranged between the positive and negative electrodes to isolate the positive and negative electrodes. The separator can be a polyolefin, such as polyethylene, polypropylene, a composite of polyethylene and polypropylene, or a sheet formed by glass fiber and a non-woven fabric. When a solid electrolyte is used, the solid electrolyte can also be used as a separator.
[0067] Next, the preparation method of the lithium battery is described, which is used to prepare the above-mentioned lithium battery. The main steps include: mixing the positive electrode material, conductive agent, binder and solvent of the lithium battery evenly and coating it on at least one surface of the positive electrode current collector, drying, rolling and slicing it as the positive electrode; mixing the negative electrode material, conductive agent, binder and solvent evenly and coating it on at least one surface of the negative electrode current collector, drying, rolling and slicing it as the negative electrode; assembling the positive electrode sheet, separator and negative electrode sheet into a stacked or wound battery cell, placing the battery cell in a shell, injecting electrolyte and then packaging it to obtain a lithium battery.
[0068] In the above-mentioned positive or negative electrode sheets, the amounts of the positive and negative electrode materials, conductive agents, and binders are not specifically limited. For example, based on the total amount of the positive or negative electrode materials, the mass content of the lithium battery positive electrode material or negative electrode material can be 50%-99%, the mass content of the conductive agent can be 0.5%-25%, and the mass content of the binder can be 0.5%-25%.
[0069] For year-on-year calculation, the mass ratio of the positive electrode material of the lithium battery: the conductive agent: the binder in the embodiment of the present invention is 90:5:5, the conductive agent is acetylene black, the binder is polyvinylidene fluoride (PVDF), the negative electrode in the button half-cell is metallic lithium, the negative electrode material in the soft-pack full battery is graphite, the conductive agent is acetylene black, the binder is sodium carboxymethyl cellulose (CMC) and styrene-butadiene rubber (SBR), wherein graphite: acetylene black: CMC: SBR = 95:1.5:2:1.5, the diaphragm is the American Celllgard2400 polypropylene diaphragm, the electrolyte is a liquid electrolyte, the solvent is a mixed solvent of ethylene carbonate (EC) and ethyl methyl carbonate (EMC), the volume ratio of the two is 3:7, the solute is lithium hexafluorophosphate LiPF6, and the molar concentration is 1 mol / L.
[0070] The lithium battery in the embodiment of the present invention is assembled in an inert atmosphere glove box, and the moisture and oxygen content in the glove box is less than 0.1ppm. There is no special restriction on the battery model. For year-on-year comparison, the button battery model used in the embodiment of the present invention is 2025 type, the design capacity of the soft-pack full battery is 2Ah, and the electrochemical test conditions are: temperature is 25°C; voltage range is 2.8-4.3V. The thermal runaway trigger temperature of the soft-pack full battery is obtained by adiabatic accelerating calorimeter test, using heating-waiting-search mode, step temperature 10°C, waiting time 15min, search time 5min, maximum search temperature 250°C, and exothermic detection limit 0.03°C / min. The temperature corresponding to the heat release rate of the full battery reaching 1°C / min is the thermal runaway trigger temperature of the battery.
[0071] The present invention will be described in detail below through examples.
[0072] [Example 1]
[0073] This example is used to illustrate the preparation and evaluation method of the positive electrode material for a lithium battery according to the present invention.
[0074] (1) Preparation of positive electrode materials for lithium batteries
[0075] Take the chemical composition of Ni 0.8 Co 0.1 Mn0 .1 10g of (OH)2 precursor (flake, average thickness is about 30nm), add lithium source LiOH·H2O and Bi2O3, so that the molar ratio of Li: precursor is 1.02:1, and the molar ratio of Bi to precursor is 0.02:1. After the precursor, lithium source and Bi2O3 are evenly mixed, they are loaded into a crucible for step-by-step sintering. The first step is to increase the temperature from room temperature to 450℃ at 5℃ / min and keep it warm for 6h. The second step is to increase the temperature from 450℃ to 850℃ at 5℃ / min and keep it warm for 12h. Then cool it naturally to obtain the positive electrode material of lithium battery.
[0076] (2) Evaluation of positive electrode materials for lithium batteries
[0077] The SEM image of the lithium battery positive electrode material is as follows Figure 1 As shown in the figure, it can be seen that the preparation method provided by the present invention can obtain a lithium battery positive electrode material with good sphericity. The lithium battery positive electrode material is a secondary microsphere formed by the accumulation of primary particles. The medium particle size of the secondary microsphere is 10.3 μm. Figure 1 The cross-sectional view of the lithium battery positive electrode material obtained by cutting with a focused ion beam is shown in FIG. Figure 2 As shown, the primary particles of the lithium battery positive electrode material are long strips, and the primary particles are arranged and distributed along the radial direction of the secondary microspheres, and the average aspect ratio of the primary particles is 5.28.
[0078] Take the above-mentioned lithium battery positive electrode material, acetylene black and 10% polyvinylidene fluoride solution by mass, mix them evenly according to the mass ratio of lithium battery positive electrode material: acetylene black: polyvinylidene fluoride 90:5:5, apply them on aluminum foil, dry the solvent, slice and obtain the positive electrode sheet, use the lithium sheet as the counter electrode, and assemble the above-mentioned positive electrode sheet into a button lithium battery in a glove box. The charge and discharge voltage range of button lithium battery is 2.8-4.3V. The first discharge specific capacity at 0.1C rate is 201.7mAh / g, and the coulomb efficiency in the first week reaches 90.9%.
[0079] Graphite was used as the negative electrode material, and the above-mentioned positive electrode plates were assembled into a 2Ah soft-pack full battery for adiabatic accelerated calorimetry testing. The thermal runaway trigger temperature was 115.9°C.
[0080] [Example 2]
[0081] This example is used to illustrate the preparation and evaluation method of the positive electrode material for a lithium battery according to the present invention.
[0082] (1) Preparation of positive electrode materials for lithium batteries
[0083] Take the chemical composition of Ni0.8Co 0.1 10g of Mn0.1(OH)2 precursor (flake-shaped, with an average thickness of about 30nm) was added with lithium sources LiOH·H2O and Sb2O3, so that the molar ratio of Li:precursor was 1.1:1, and the molar ratio of Sb to precursor was 0.05:1. The precursor, lithium source and Sb2O3 were evenly mixed and loaded into a crucible for step-by-step sintering. The first step was to increase the temperature from room temperature to 500°C at 10°C / min and keep it warm for 6h. The second step was to increase the temperature from 500°C to 800°C at 10°C / min and keep it warm for 16h. Then, the mixture was naturally cooled to obtain a positive electrode material for a lithium battery.
[0084] (2) Evaluation of positive electrode materials for lithium batteries
[0085] SEM images of lithium battery positive electrode materials and Figure 1 Similar to Figure 2 The primary particles of the lithium battery positive electrode material are long strips, and the primary particles are arranged and distributed along the radial direction of the secondary microspheres, and the average aspect ratio of the primary particles is 4.13. The median particle size of the secondary microspheres is 10.1 μm.
[0086] A lithium battery was prepared according to the method described in Example 1.
[0087] The charging and discharging voltage range of button lithium battery is 2.8-4.3V. The first discharge capacity at 0.1C rate is 201.5mAh / g, and the first week coulomb efficiency reaches 90.7%.
[0088] Taking graphite as the negative electrode material, the above-mentioned positive electrode sheets were assembled into a 2Ah soft-pack full battery for adiabatic accelerated calorimetry testing, and the thermal runaway trigger temperature reached 115.2°C.
[0089] [Example 3]
[0090] (1) Preparation of positive electrode materials for lithium batteries
[0091] Take the chemical composition of Ni 0.8 Co 0.1 Mn0 .110g of (OH)2 precursor (flake, average thickness is about 30nm), add lithium source LiOH·H2O and P2O5, so that the molar ratio of Li: precursor is 1.1:1, and the molar ratio of P to precursor is 0.07:1. After the precursor, lithium source and P2O5 are evenly mixed, they are loaded into a crucible for step-by-step sintering. The first step is to increase the temperature from room temperature to 550℃ at 5℃ / min and keep it warm for 4h. The second step is to increase the temperature from 550℃ to 750℃ at 10℃ / min and keep it warm for 24h. Then cool it naturally to obtain the positive electrode material of lithium battery.
[0092] (2) Evaluation of positive electrode materials for lithium batteries
[0093] SEM images of lithium battery positive electrode materials and Figure 1 Similar to Figure 2 The primary particles of the lithium battery positive electrode material are long strips, and the primary particles are arranged and distributed along the radial direction of the secondary microspheres, and the average aspect ratio of the primary particles is 2.75. The median particle size of the secondary microspheres is 9.8 μm.
[0094] A lithium battery was prepared according to the method described in Example 1.
[0095] The charging and discharging voltage range of button lithium battery is 2.8-4.3V. The first discharge capacity at 0.1C rate is 199.7mAh / g, and the first week coulomb efficiency reaches 90.1%.
[0096] Taking graphite as the negative electrode material, the above-mentioned positive electrode sheets were assembled into a 2Ah soft-pack full battery for adiabatic accelerated calorimetry testing, and the thermal runaway trigger temperature reached 112.2°C.
[0097] [Example 4]
[0098] (1) Preparation of positive electrode materials for lithium batteries
[0099] Take the chemical composition of Ni 0.8 Co 0.15 Al 0.05 10g of (OH)2 precursor (flake, average thickness is about 50nm), add lithium source LiOH·H2O and P2O5, so that the molar ratio of Li: precursor is 1.1:1, and the molar ratio of P to precursor is 0.1:1. After the precursor, lithium source and P2O5 are evenly mixed, they are loaded into a crucible for step-by-step sintering. The first step is to increase the temperature from room temperature to 550℃ at 5℃ / min and keep it warm for 4h. The second step is to increase the temperature from 550℃ to 750℃ at 10℃ / min and keep it warm for 9h. Then, it is cooled naturally to obtain the positive electrode material of lithium battery.
[0100] (2) Evaluation of positive electrode materials for lithium batteries
[0101] SEM images of lithium battery positive electrode materials and Figure 1Similar to Figure 2 The primary particles of the lithium battery positive electrode material are long strips, and the primary particles are arranged and distributed along the radial direction of the secondary microspheres, and the average aspect ratio of the primary particles is 1.95. The median particle size of the secondary microspheres is 9.6 μm.
[0102] A lithium battery was prepared according to the method described in Example 1.
[0103] The charging and discharging voltage range of button lithium battery is 2.8-4.3V. The first discharge capacity at 0.1C rate is 197.3mAh / g, and the first week coulomb efficiency reaches 89.5%.
[0104] Taking graphite as the negative electrode material, the above-mentioned positive electrode plates were assembled into a 2Ah soft-pack full battery for adiabatic accelerated calorimetry testing, and the thermal runaway trigger temperature reached 111.6°C.
[0105] [Example 5]
[0106] (1) Preparation of positive electrode materials for lithium batteries
[0107] Take the chemical composition of Ni 0.8 Co 0.1 Mn0 .1 10g of (OH)2 precursor (flake, average thickness is about 30nm), add lithium source LiOH·H2O and P2O5, so that the molar ratio of Li: precursor is 1.1:1, and the molar ratio of P to precursor is 0.03:1. After the precursor, lithium source and P2O5 are evenly mixed, they are loaded into a crucible for step-by-step sintering. The first step is to increase the temperature from room temperature to 500℃ at 5℃ / min and keep it warm for 4h. The second step is to increase the temperature from 500℃ to 750℃ at 10℃ / min and keep it warm for 12h. Then cool it naturally to obtain the positive electrode material of lithium battery.
[0108] (2) Evaluation of positive electrode materials for lithium batteries
[0109] SEM images of lithium battery positive electrode materials and Figure 1 Similar to Figure 2 The primary particles of the lithium battery positive electrode material are long strips, and the primary particles are arranged and distributed along the radial direction of the secondary microspheres, and the average aspect ratio of the primary particles is 3.35. The median particle size of the secondary microspheres is 10.4 μm.
[0110] A lithium battery was prepared according to the method described in Example 1.
[0111] The charging and discharging voltage range of button lithium battery is 2.8-4.3V. The first discharge capacity at 0.1C rate is 200.3mAh / g, and the first week coulomb efficiency reaches 90.2%.
[0112] Taking graphite as the negative electrode material, the above-mentioned positive electrode sheets were assembled into a 2Ah soft-pack full battery for adiabatic accelerated calorimetry testing, and the thermal runaway trigger temperature reached 114.3°C.
[0113] [Comparative Example 1]
[0114] (1) Preparation of positive electrode materials for lithium batteries
[0115] Take the chemical composition of Ni0.8Co0.1Mn0 .1 10g of (OH)2 precursor (flake-shaped, with an average thickness of about 30nm) was added with lithium source LiOH·H2O so that the molar ratio of Li:precursor was 1.02:1. The precursor and lithium source were mixed evenly and loaded into a crucible for step-by-step sintering. The first step was to increase the temperature from room temperature to 450℃ at 5℃ / min and keep it warm for 6h. The second step was to increase the temperature from 450℃ to 850℃ at 5℃ / min and keep it warm for 12h. The cathode material of the lithium battery was then cooled naturally to obtain the cathode material.
[0116] (2) Evaluation of positive electrode materials for lithium batteries
[0117] SEM images of lithium battery positive electrode materials and Figure 1 The cross-sectional image obtained after focused ion beam cutting shows that the primary particles of the positive electrode material of the lithium battery are short and thick particles. The primary particles have no specific arrangement and are in a disordered stacking state. The average aspect ratio of the primary particles is 1.22. The median particle size of the secondary microspheres is 9.8μm.
[0118] A lithium battery was prepared according to the method described in Example 1.
[0119] The charging and discharging voltage range of button lithium battery is 2.8-4.3V. The first discharge capacity at 0.1C rate is 195.3mAh / g, and the first week coulomb efficiency reaches 87.1%.
[0120] Graphite was used as the negative electrode material, and the above-mentioned positive electrode plates were assembled into a 2Ah soft-pack full battery for adiabatic accelerated calorimetry testing. The thermal runaway trigger temperature was 108.7°C.
[0121] [Comparative Example 2]
[0122] (1) Preparation of positive electrode materials for lithium batteries
[0123] Compared with Example 1, the difference is that the precursor morphology is that the primary particles are microspheres formed by spindle agglomeration.
[0124] (2) Evaluation of positive materials for lithium batteries
[0125] SEM images of lithium battery positive electrode materials and Figure 1Similarly, the cross-sectional image obtained after focused ion beam cutting shows that the primary particles of the lithium battery positive electrode material are short and thick particles. The primary particles have no specific arrangement and are in a disordered stacking state. The average aspect ratio of the primary particles is 1.30. The median particle size of the secondary microspheres is 10.3μm.
[0126] A lithium battery was prepared according to the method described in Example 1.
[0127] The charging and discharging voltage range of button lithium battery is 2.8-4.3V. The first discharge capacity at 0.1C rate is 193.5mAh / g, and the first week coulomb efficiency reaches 87.3%.
[0128] Taking graphite as the negative electrode material, the above-mentioned positive electrode sheets were assembled into a 2Ah soft-pack full battery for adiabatic accelerated calorimetry testing, and the thermal runaway trigger temperature reached 108.9°C.
[0129] Table 1 Electrochemical performance test results of lithium batteries obtained in each example
[0130]
[0131] Table 2 Aspect ratio of primary particles in the positive electrode materials obtained in each example
[0132] Primary particle aspect ratio Example 1 5.28 Example 2 4.13 Example 3 2.75 Example 4 1.95 Example 5 3.35 Comparative Example 1 1.22 Comparative Example 2 1.30
[0133] The above describes the specific implementation of the present invention in detail, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the various technical features being combined in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A lithium battery cathode material, comprising a compound with a chemical composition of Li a Ni x Co y M z N p O2, where 0.9 ≤ a ≤ 1.2, 0 ≤ x ≤ 1, 0 ≤ y ≤ 1, 0 ≤ z ≤ 1, 0 < p ≤ 0.1, x, y, and z are not all 0 at the same time, and the values of a, x, y, z, and p satisfy the principle of electroneutrality. The M is selected from at least one element of Group VIIB or Group IIIA, and the N is selected from at least one element of Group VA; the lithium battery cathode material is spherical, and the primary particles are strip-shaped with an aspect ratio of 1.05 - 20.
00.
2. The positive electrode material for lithium battery according to claim 1, characterized in that: The chemical composition is Li a Ni x Co y M z N p compound of O2, 0.5 ≤ x ≤ 0.95, 0 ≤ y ≤ 0.5, 0 ≤ z ≤ 0.5, 0 < p ≤ 0.05, x, y, and z are not all 0 at the same time, preferably x, y, and z are not 0, and the values of a, x, y, z, and p satisfy the principle of electroneutrality.
3. The positive electrode material for lithium battery according to claim 1, characterized in that: The primary particles are arranged along the radial direction of the sphere, and the median particle size of the spherical particles is 1-20 μm.
4. The lithium battery positive electrode material according to claim 1 or 3, characterized in that: The aspect ratio of the primary particles is 1.50-10.00, preferably 1.50-8.
00.
5. The method for preparing the positive electrode material for a lithium battery according to any one of claims 1 to 4, comprising: The positive electrode material precursor, the lithium source and the modifier containing the VA group element are mixed and sintered to obtain the lithium battery positive electrode material.
6. The preparation method according to claim 5, characterized in that: The chemical composition of the positive electrode material precursor is Ni x Co y M z (OH)2, 0≤x≤1, 0≤y≤1, 0≤z≤1, preferably 0.5≤x≤0.95, 0≤y≤0.5, 0≤z≤0.5, the values of x, y and z are not 0 at the same time, and the values of x, y and z satisfy the principle of electrical neutrality.
7. The preparation method according to claim 5, characterized in that: The lithium source is preferably selected from at least one of lithium nitrate, lithium chloride, lithium carbonate, lithium hydroxide, lithium hydroxide monohydrate, lithium oxide, lithium acetate and lithium oxalate; And / or, the modifier containing a Group VA element is selected from at least one of nitrates, chlorides, carbonates, hydroxides, oxides, acetates and oxalates containing a Group VA element.
8. The preparation method according to claim 5, characterized in that: The molar ratio of the positive electrode material precursor to the lithium source is 1:(0.9-1.2) based on the Li element; And / or, the molar ratio of the positive electrode material precursor and the modifier containing the Group VA element is 1:(0-0.1) and not 0, preferably 1:(0.001-0.05) in terms of the Group VA element.
9. The preparation method according to claim 5, characterized in that: The sintering temperature is 600-1000° C., preferably 720-900° C., and the sintering time is 4-48 h, preferably 8-24 h, and more preferably 12-20 h.
10. The preparation method according to claim 5, characterized in that: The morphology of the positive electrode material precursor is microspheres formed by flake accumulation; the average thickness of the flakes is 1-500nm, preferably 1-200nm.
11. Use of the lithium battery positive electrode material according to any one of claims 1 to 4 in lithium batteries.